ANALISA CHROME DEPOSIT DAN HARDNESS PADA PROSES HARD CHROME DENGAN VARIASI ARUS UNTUK RODA GIGI SEPEDA MOTOR - Basuki Widodo; Wahyu Panji Asmoro (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
Most of common public equalizes term chrome metal bedding type cum all. When we call elektroplating which meraka intention is chrome. Chrome is metal bedding but in the application of his(its is applied in the form of solit like: mobil/motor, engine block awning, bumper and other aksesoris. Fundamental bedding applies nipple plating, that is layering metal with nipple base material this thing aim to get smooth equiamplitude surface and gleams. Just nipple doesn't make equiamplitude surface of metal arranged in layers gleams. After arranged in layers with chrome then equiamplitude surface of metal arranged in layers gleams glittering like at a mirror. In bedding of hard chrome it is important to know how big level of hardness to be gotten better bedding result, besides need to be known thickness of deposit so that can protect substance from friction with other substance. At this research done various current when bedding process of hard chrome. Current applied is 15 Amperes, 20 Amperes, 25 Amperes at temperature 450 C. Is expected with existence of various current can yield level of varying hardness and thickness, so that knowable influence various current at process chrome at gear product. From result of research it is got that ever greater of current given increasingly downwards level of the hardness. So do with the thickness is ever greater is current which in giving, increasingly the chrome layer thick.